The Psychological Adaptation of the Deaf and Hard of Hearing Students - Rakan Radi Alhrahsheh, Husian Alserhan, (Opción, 2019)
This study focuses on the psychological and social adaptation of the deaf and hard of hearing (DHH) students in the University. The method that has been used as the social survey within an intended non-random sample of 38 DHH in al-Ain University (2018/2019). The results indicated that there were statistically significant differences at (a=0.05) in the scores of the psychological and social adaptation level attributed to the marital status variable. The study concluded that the students were happy and motivated to study and the level of the students’ psychological and social adaptation in the University was medium.